High-mildew-resistance and high-fluidity photovoltaic glass mildew-resistant powder and preparation method thereof

By using acrylate monomers and other materials in photovoltaic glass anti-mold powder, it is prepared with uniform particle size and moderate hardness, and combined with organic acids, inorganic acids and inorganic nanomaterials, it has solved the problem of anti-mold in the existing technology. The problems of insufficient properties and uneven distribution of microspheres have achieved efficient anti-mold and scratch resistance.

CN119463011APending Publication Date: 2025-02-18YUNYAN MATERIALS TECH (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411679593.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing photovoltaic glass anti-mold isolation powder has insufficient durability, and the isolation microspheres are not prepared enough, and the microspheres are unevenly distributed, which can easily scratch the glass. The anti-mold powder has insufficient fluidity and low powder efficiency.

Method used

Solid isolation microspheres composed of acrylate monomers, styrene monomers, initiators and crosslinking agents are prepared by specific preparation methods to prepare isolation microspheres with uniform particle size and moderate hardness, and are combined with organic acids and inorganic The combination of acid and inorganic nanomaterials makes high-mold-proof and high-flowability photovoltaic glass anti-mold powder.

Benefits of technology

Effectively prevent mold and scratching of photovoltaic glass, improve mold resistance durability, improve the spherical shape and distribution uniformity of microspheres, enhance the fluidity and powder sprinkling efficiency of anti-mold powder, and comply with the JC/T1008-2018 standard scratch resistance .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005147967460000031
    Figure FDA0005147967460000031
Patent Text Reader

Abstract

The invention discloses high-mildew-resistance and high-fluidity photovoltaic glass mildew-proof powder and a preparation method thereof.The high-mildew-resistance and high-fluidity photovoltaic glass mildew-proof powder comprises isolation microspheres, the isolation microspheres are solid spheres composed of polymers, and the raw materials for preparing the isolation microspheres comprise, by weight, 1-5 parts of a curing agent, 1-5 parts of a curing agent, 1-5 parts of a curing agent and 1-5 parts of a curing agent. The particle size of the isolation microsphere is 100-250 [mu] m, and the isolation microsphere is moderate in hardness, narrow in particle size distribution, smooth in surface, free of defects, resistant to a certain temperature and good in fluidity. The photovoltaic glass mildew-proof powder provided by the invention can effectively prevent the photovoltaic glass from being scratched in a mildewed transportation process, and can continuously prevent the glass from mildewing when being prepared into the mildew-proof powder together with mildew-proof components such as organic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to photovoltaic glass mildew-proof powder with high mildew-proofness and high fluidity, and a preparation method thereof. Background Art

[0002] If photovoltaic glass products are not stored and transported properly, they will be scratched or corroded (mold) due to friction between the glass, affecting the final use of the glass and causing serious economic losses.

[0003] Photovoltaic glass mold generally goes through the following process: water or moisture adsorbed on the surface of photovoltaic glass; water or moisture diffused into the glass; soluble silicates in the surface layer were hydrolyzed and destroyed, first sodium silicate and potassium silicate were hydrolyzed and destroyed, forming caustic soda (NaOH) and separating SiO2; the separated SiO2 formed silica gel, forming a protective film on the surface of photovoltaic glass, which prevented further erosion; the caustic soda formed by hydrolysis reacted with carbon dioxide in the air to form sodium carbonate, which gathered on the surface of the glass and formed soluble salts in the surface film. Due to its strong hygroscopicity, it absorbed water and deliquesced, and finally formed small droplets of alkali liquid. When the small droplets were in contact with the glass for a long time, the gel-like silica film could be partially dissolved in it, causing serious local erosion on the glass surface and forming spots. In the early stage of glass mold, the surface will have a slight roughness, the glass is difficult to clean, and it is easy to get dust; small spots will appear after that, and severe flakes, filaments and foggy patches will appear; rainbows will appear, the hand feel will be rough, and the smoothness and transparency of the glass will be significantly reduced. Mold will cause irreversible effects on photovoltaic glass: mechanical strength is reduced, optical performance is affected, appearance is deteriorated, flakes appear in the packaging box, and it cannot be used for deep processing of glass such as coated glass. Therefore, effective measures need to be taken to prevent glass mold.

[0004] In addition, finished photovoltaic glass panels need to be packaged before storage after shipment. To prevent the photovoltaic glass surface from being scratched and damaged, an isolation layer should be placed between two adjacent photovoltaic glass sheets during packaging. However, the isolation layer alone cannot effectively prevent the photovoltaic glass surface from being damaged. Generally, it is applied on the surface of the photovoltaic glass panels before packaging. Photovoltaic glass mildew-proof powder (also known as "glass mildew-proof isolation powder") is evenly applied to the glass surface to solve the problem of scratches and mildew on the glass surface caused by vibration and extrusion during transportation.

[0005] The current photovoltaic glass mildew-proof isolation powder generally includes components such as high molecular polymers, acidic materials, and inorganic nanomaterials. However, the existing glass mildew-proof isolation powder has the following shortcomings: insufficient mildew-proof durability, the isolation microspheres are not spherical enough, the microspheres are unevenly distributed, the span is large, and the span is above 1.1, which can easily scratch the glass. The mildew-proof powder has insufficient fluidity and low powder spreading efficiency. Summary of the invention

[0006] On one hand, the present invention provides a photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity, which can effectively prevent the photovoltaic glass from mildewing and scratching. To achieve the purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0007] A photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity, the photovoltaic glass mildew-proof powder comprising isolation microspheres, the isolation microspheres being solid spheres composed of polymers, and the raw materials for preparing the isolation microspheres comprising the following components in parts by weight:

[0008] 60-120 parts of acrylic acid ester monomer,

[0009] 0-35 parts of styrene monomer,

[0010] Initiator 0.01-2 parts,

[0011] 1 to 10 parts of crosslinking agent.

[0012] In another preferred embodiment, based on the total weight of the photovoltaic glass mildew-proof powder, the mass percentage of the isolation microspheres is 30% to 70%.

[0013] In another preferred embodiment, the raw material for preparing the spacer microspheres contains 75 to 100 parts by weight of acrylic acid ester monomers.

[0014] In another preferred embodiment, the raw material for preparing the spacer microspheres contains 0 to 25 parts by weight of styrene monomers.

[0015] In another preferred embodiment, the raw materials for preparing the spacer microspheres contain 0.3 to 0.6 parts by weight of the initiator.

[0016] In another preferred embodiment, the raw materials for preparing the spacer microspheres contain 3 to 6 parts by weight of the initiator.

[0017] In another preferred embodiment, the particle size of the spacer microspheres is 100-250 μm. In another more preferred embodiment, the particle size of the spacer microspheres is 140-200 μm.

[0018] In another preferred embodiment, the hardness of the spacer microspheres is Shore D 70-100. In another more preferred embodiment, the hardness of the spacer microspheres is Shore D 80-90.

[0019] In another preferred embodiment, the tolerable temperature of the spacer microspheres is -20 to 120° C. In another more preferred embodiment, the tolerable temperature of the spacer microspheres is -40 to 100° C.

[0020] In another preferred embodiment, the particle size span of the spacer microspheres is 0.5-0.9. In another more preferred embodiment, the particle size span of the spacer microspheres is 0.65-0.85.

[0021] In another preferred embodiment, the acrylic monomer is selected from methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isobornyl methacrylate, or a combination thereof. In another more preferred embodiment, the acrylic monomer is selected from methyl methacrylate or methyl acrylate.

[0022] In another preferred embodiment, the styrene monomer is selected from styrene, methyl styrene, or a combination thereof.

[0023] In another preferred embodiment, the initiator is selected from azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dodecanoyl peroxide, or a combination thereof.

[0024] In another preferred embodiment, the crosslinking agent is a crosslinking agent with trifunctionality or above. In another preferred embodiment, the crosslinking agent is selected from triallyl cyanurate, triallyl isocyanurate, ethylene glycol dimethacrylate, trimethylallyl isocyanate and trimethylolpropane trimethacrylate, or a combination thereof.

[0025] In another preferred embodiment, the raw materials for preparing the spacer microspheres further include the following components in parts by weight:

[0026] 10-20 parts of dispersion stabilizer,

[0027] Inhibitor 0.1-1 part.

[0028] In another preferred embodiment, the dispersion stabilizer is selected from polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and polyvinyl pyrrolidone, or a combination thereof.

[0029] In another preferred embodiment, the inhibitor is selected from sodium nitrite, methylene blue, sodium sulfide, thiourea, sodium sulfate, ammonium thiocyanate, or a combination thereof, more preferably sodium nitrite.

[0030] In another preferred embodiment, the method for preparing the isolated microspheres comprises the following steps:

[0031] (1) Preparation of oil phase: 60 to 120 parts by weight of acrylate monomer, 0 to 35 parts by weight of styrene monomer, 0.01 to 2 parts by weight of initiator and 0.05 to 10 parts by weight of crosslinking agent are mixed at 0 to 40° C. to prepare an oil phase;

[0032] (2) Preparation of aqueous phase: Add 10 to 20 parts by weight of a dispersion stabilizer and 0.1 to 1 part by weight of a polymerization inhibitor to 150 to 250 parts by weight of deionized water, and stir to form an aqueous phase;

[0033] (3) homogenizing the water-oil phase: pouring the oil phase prepared in step (1) into the water phase prepared in step (2), and homogenizing the mixed liquid to form a suspension;

[0034] (4) Preparation of microsphere reaction: The suspension obtained in step (3) is transferred into a reaction vessel and reacted at 40-100° C. for 15-30 h in an inert gas atmosphere. The milky white liquid obtained after the reaction is filtered, washed with deionized water, and then dried to obtain the isolated microspheres.

[0035] In another preferred embodiment, in the preparation method, in step (3), homogenization is performed using a homogenization device, the homogenization speed is 200 to 1000 rpm, and the homogenization time is 10 to 40 min.

[0036] In another preferred embodiment, in the preparation method, in step (4), the inert gas is selected from nitrogen, argon or helium.

[0037] In another preferred embodiment, the photovoltaic glass mildew-proof powder includes the following components in percentage by weight:

[0038] Isolation microspheres 30-70%,

[0039] Organic acid 5-30%,

[0040] Inorganic acid 20-60%,

[0041] Inorganic nanomaterials 0.5-5%.

[0042] In another preferred embodiment, the organic acid is selected from maleic acid, adipic acid, cyclohexylbutyric acid, and fumaric acid. In another more preferred embodiment, the organic acid is selected from adipic acid.

[0043] In another preferred embodiment, the inorganic acid is selected from boric acid and tartaric acid. In another more preferred embodiment, the inorganic acid is selected from boric acid.

[0044] In another preferred embodiment, the inorganic nanomaterial is selected from fumed silica and nano calcium carbonate. In another preferred embodiment, the inorganic nanomaterial is selected from fumed silica.

[0045] The present invention also provides a method for preparing the photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity. The preparation method comprises uniformly mixing the components according to the dosage. DETAILED DESCRIPTION

[0046] In view of the problems existing in the photovoltaic glass mildew-proof powder in the prior art, the inventors of the present application have found through in-depth research that in the process of preparing the photovoltaic glass mildew-proof powder, adding solid isolation microspheres with uniform particle size and moderate hardness prepared by the present invention can effectively prevent the photovoltaic glass from being scratched during transportation due to mildew. When mixed with mildew-proof ingredients such as organic acids to form mildew-proof powder, it can sustainably prevent the glass from being moldy.

[0047] The acrylic monomer used to prepare the isolation microspheres serves as the main component for polymerization into spherical isolation microspheres. The acrylic monomers that can be used in the present invention include but are not limited to methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isooctyl acrylate, isooctyl methacrylate, and isobornyl methacrylate.

[0048] The styrene monomer used to prepare the isolation microspheres serves as an auxiliary component for polymerization into spherical isolation microspheres, and can fine-tune the surface hardness of the microspheres. The styrene monomers that can be used in the present invention include but are not limited to styrene and methyl styrene.

[0049] The initiator used to prepare the isolation microspheres is used to initiate polymerization of monomers to form microspheres. The initiators that can be used in the present invention include but are not limited to azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and dodecanoyl peroxide.

[0050] The role of the cross-linking agent used to prepare the isolation microspheres is to adjust the overall hardness of the microspheres and improve the scratch resistance. The cross-linking agent that can be used in the present invention is preferably a cross-linking agent with trifunctionality or above, for example, triallyl cyanurate, triallyl isocyanurate, trimethallyl isocyanate and trimethylolpropane trimethacrylate.

[0051] In the photovoltaic glass mildew-proof powder with high mildew-proofness and high fluidity of the present invention, the organic acid provides mildew-proof performance. The organic acid used includes but is not limited to maleic acid, adipic acid, cyclohexylbutyric acid, and fumaric acid.

[0052] In the photovoltaic glass mildew-proof powder with high mildew-proofness and high fluidity of the present invention, the role of the inorganic acid is to cooperate with the organic acid to provide mildew-proof performance. The inorganic acid used includes but is not limited to boric acid and tartaric acid.

[0053] In the photovoltaic glass mildew-proof powder with high mildew-proofness and high fluidity of the present invention, the inorganic nanomaterials are used to balance the performance of the microspheres, organic acids and inorganic acids. The inorganic nanomaterials used include but are not limited to fumed silica and nano calcium carbonate.

[0054] In some specific implementations, in the photovoltaic glass mildew-proof powder of the present invention, the overall hardness of the isolation microspheres is Shore D80-90, and the overall hardness is moderate, which can prevent the isolation microspheres from being deformed by excessive pressure between the glass and losing their isolation effect.

[0055] In some specific implementations, in the photovoltaic glass mildew-proof powder of the present invention, the surface hardness of the isolation microspheres is HB-1H, which is moderate and will not cause scratches on the glass surface.

[0056] In some specific implementations, in the photovoltaic glass mildew-proof powder of the present invention, the isolation microspheres have a tolerable temperature of -40-100°C.

[0057] In the process of preparing the isolation microspheres of the present invention, the function of the dispersion stabilizer is to make the prepared microspheres uniform and uniform. The dispersion stabilizer used in the present invention includes but is not limited to polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and polyvinyl pyrrolidone. The polymerization inhibitor used in the present invention includes but is not limited to sodium nitrite, methylene blue, sodium sulfide, thiourea, sodium sulfate, and ammonium thiocyanate.

[0058] In the high mildew resistance and high fluidity photovoltaic glass mildew resistance powder of the present invention, the role of the inhibitor is to prevent a small part of the monomers that enter the water phase from polymerizing and affecting the appearance of the microspheres. The inhibitors used in the present invention include but are not limited to sodium nitrite, methylene blue, sodium sulfide, thiourea, sodium sulfate and ammonium thiocyanate.

[0059] The isolation microspheres in the photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity of the present invention are uniform solid spheres, with moderate overall hardness and surface hardness, narrow particle size distribution with a span of 0.5-0.9, smooth surface, resistance to certain temperature, and applicable temperature range of -40-100°C.

[0060] The hardness, particle size distribution and smooth surface of the isolation microspheres used in the present invention are suitable for forming an effective isolation layer between photovoltaic glasses, and have excellent scratch resistance. At the same time, the combination of inorganic acids, organic acids and inorganic nanomaterials makes the photovoltaic glass have long-lasting mildew resistance.

[0061] The present invention is described below in conjunction with specific embodiments, but the present invention is not limited to the scope of these embodiments. Unless otherwise specified, ratios, proportions, parts, percentages in the present invention are all by weight, and all temperatures are degrees Celsius.

[0062] The photovoltaic glass used in the following examples is commercially available photovoltaic glass (Ancai High-Tech)

[0063] In the following embodiments, the average particle size of the isolated microspheres is measured by the Best Laser Particle Size Analyzer 2600 test (reference standard GB / T 19077); the span is measured / calculated by the Best Laser Particle Size Analyzer 2600 test (reference standard GB / T 19077); the overall hardness is measured by the Shore durometer test; the surface hardness is measured by the pencil hardness test, and the temperature resistance is measured by the TMA test.

[0064] Example 1

[0065] The preparation method of the isolated microspheres comprises the following steps:

[0066] (1) Preparation of oil phase: 100 g of methyl methacrylate, 3 g of triallyl cyanurate and 0.5 g of azobisisobutyronitrile were mixed and stirred at 20° C. for 10 min to form a uniform oil phase;

[0067] (2) Preparation of aqueous phase: 12 g of polyvinyl alcohol was dissolved in 200 g of deionized water, and 0.25 g of sodium nitrite was added and stirred evenly. The resulting solution was the aqueous phase.

[0068] (3) Homogenization of water and oil phases: Pour the oil phase into the water phase, and stir the mixed liquid at 300 rpm for 10 min to form a suspension;

[0069] (4) Preparation of isolated microspheres by reaction: The above suspension was transferred into a reactor and reacted at 70°C for 20 hours in a nitrogen atmosphere. The milky white liquid obtained after the reaction was filtered and washed with deionized water and then dried to obtain microspheres with an average particle size of 200 μm, a span of 0.85, an overall hardness of Shore D85, and a temperature resistance of -40-98°C.

[0070] Example 2

[0071] The preparation method of the isolated microspheres comprises the following steps:

[0072] (1) Preparation of oil phase: 75 g of methyl methacrylate, 25 g of styrene, 3 g of trimethylolpropane trimethacrylate and 0.6 g of benzoyl peroxide were mixed and stirred at 20° C. for 10 min to form a uniform oil phase;

[0073] (2) Preparation of aqueous phase: 16 g of hydroxyethyl cellulose was dissolved in 200 g of deionized water, and 0.2 g of sodium nitrite was added and stirred evenly. The resulting solution was the aqueous phase.

[0074] (3) Homogenization of water and oil phases: Pour the oil phase into the water phase, and stir the mixed liquid at 500 rpm for 30 min to form a suspension;

[0075] (4) Preparation of isolated microspheres by reaction: The above suspension was transferred into a reactor and reacted at 80°C for 18 hours in a nitrogen atmosphere. The milky white liquid obtained after the reaction was filtered and washed with deionized water and then dried to obtain isolated microspheres with an average particle size of 150 μm, a span of 0.75, an overall hardness of Shore D90, a surface hardness of 1H, and a temperature resistance of -40°C to 100°C.

[0076] Example 3

[0077] The preparation method of the isolated microspheres comprises the following steps:

[0078] (1) Preparation of oil phase: 53 g of methyl methacrylate, 22 g of isooctyl methacrylate, 25 g of styrene, 6 g of trimethylallyl isocyanate and 0.6 g of dodecyl peroxide were mixed and stirred at 20° C. for 10 min to form a uniform oil phase;

[0079] (2) Preparation of aqueous phase: 14 g of polyvinyl pyrrolidone was dissolved in 200 g of deionized water, and 0.2 g of sodium nitrite was added and stirred evenly. The resulting solution was the aqueous phase.

[0080] (3) Homogenization of water and oil phases: Pour the oil phase into the water phase, and stir the mixed liquid at 800 rpm for 30 min to form a suspension;

[0081] (4) Preparation of isolated microspheres by reaction: The above suspension was transferred into a reactor and reacted at 70°C for 15 hours in a nitrogen atmosphere. The milky white liquid obtained after the reaction was filtered and washed with deionized water and then dried to obtain isolated microspheres with an average particle size of 120 μm and a span of 0.77. The overall hardness was Shore D80, the surface hardness was HB, and the temperature resistance was -40°C to 90°C.

[0082] Example 4

[0083] The preparation method of the isolated microspheres comprises the following steps:

[0084] (1) Preparation of oil phase: 86 g of methyl acrylate, 14 g of styrene, 3 g of triallyl isocyanurate, 0.2 g of azobisisobutyronitrile, and 0.1 g of azobisisoheptanenitrile were mixed and stirred at 20° C. for 10 min to form a uniform oil phase;

[0085] (2) Preparation of aqueous phase: 8 g of polyvinyl alcohol and 5 g of hydroxyethyl cellulose were dissolved in 200 g of deionized water, and 0.4 g of sodium sulfide was added and stirred evenly. The resulting solution was the aqueous phase.

[0086] (3) Homogenization of water and oil phases: Pour the oil phase into the water phase, and disperse the mixed liquid at 600 rpm for 20 min to form a suspension;

[0087] (4) Preparation of heat-expandable microspheres by reaction: The above suspension was transferred into a reactor and reacted at 60°C for 16 hours in a nitrogen atmosphere. The milky white liquid obtained after the reaction was filtered and washed with deionized water and then dried to obtain isolated microspheres with an average particle size of 140 μm and a span of 0.68. The overall hardness was Shore D90, the surface hardness was 1H, and the temperature resistance was -40°C to 100°C.

[0088] Example 5

[0089] Preparation of Anti-mildew Powder for Photovoltaic Glass

[0090] 50 g of the isolation microspheres prepared in Example 1 were uniformly mixed with 40 g of boric acid, 9 g of maleic acid and 1 g of fumed silica to prepare photovoltaic glass mildew-proof powder.

[0091] For photovoltaic glass surface, usage 0.4g / m 2 The mold time is 3 times the basic mold time, and the anti-scratch performance meets the JC / T1008-2018 standard.

[0092] (The basic mold time is the mold time of photovoltaic glass without anti-mold powder)

[0093] Example 6

[0094] Photovoltaic glass anti-mold powder

[0095] 40 g of the isolation microspheres prepared in Example 2 were uniformly mixed with 40 g of boric acid, 18 g of adipic acid, and 2 g of fumed silica to prepare photovoltaic glass mildew-proof powder.

[0096] For photovoltaic glass surface, usage 0.4g / m 2 The mildew time is 3.5 times the basic mildew time, and the anti-scratch performance meets the JC / T1008-2018 standard.

[0097] Example 7

[0098] Photovoltaic glass anti-mold powder

[0099] 52 g of the isolation microspheres prepared in Example 3 were uniformly mixed with 28 g of tartaric acid, 15 g of adipic acid, and 5 g of gas-phase nano-calcium carbonate to prepare photovoltaic glass mildew-proof powder.

[0100] For photovoltaic glass surface, usage 0.4g / m 2 The mildew time is 3.2 times of the basic mildew time, and the anti-scratch performance meets the JC / T1008-2018 standard.

[0101] Example 8

[0102] Photovoltaic glass anti-mold powder

[0103] 50 g of the isolation microspheres prepared in Example 4 were uniformly mixed with 30 g of tartaric acid, 17 g of adipic acid, and 3 g of fumed silica to prepare photovoltaic glass mildew-proof powder.

[0104] For photovoltaic glass surface, usage 0.4g / m 2 The mildew time is 3.5 times the basic mildew time, and the anti-scratch performance meets the JC / T1008-2018 standard.

[0105] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. A photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity, characterized in that: The photovoltaic glass mildew-proof powder comprises isolation microspheres, which are solid spheres composed of polymers. The raw materials for preparing the isolation microspheres comprise the following components in parts by weight: 60-120 parts of acrylic acid ester monomer, 0-35 parts of styrene monomer, Initiator 0.01-2 parts, 1 to 10 parts of crosslinking agent.

2. The photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity according to claim 1, characterized in that: The mass percentage of the isolation microspheres is 30-70% based on the total weight of the photovoltaic glass mildew-proof powder, and / or The raw materials for preparing the spacer microspheres contain 75 to 100 parts by weight of acrylic acid ester monomers, and / or The raw material for preparing the spacer microspheres contains 0 to 25 parts by weight of styrene monomers, and / or The raw materials for preparing the isolated microspheres contain 0.3 to 0.6 parts by weight of the initiator, and / or The raw materials for preparing the isolated microspheres contain 3 to 6 parts by weight of the initiator.

3. The photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity according to claim 1 or 2, characterized in that: The particle size of the isolated microspheres is 100 to 250 μm, preferably 140 to 200 μm and / or The hardness of the isolation microspheres is Shore D70-100, preferably Shore D80-90, and / or The isolation microspheres have a temperature tolerance of -20 to 120°C, preferably -40 to 100°C, and / or The particle size of the isolated microspheres ranges from 0.5 to 0.9, more preferably from 0.68 to 0.

85.

4. The photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity according to claim 1 or 2, characterized in that: The acrylic monomer is selected from methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isobornyl methacrylate, or a combination thereof, preferably isooctyl acrylate, and / or The styrene monomer is selected from styrene, methyl styrene, or a combination thereof, more preferably styrene, and / or The initiator is selected from azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dodecanoyl peroxide, or a combination thereof, and / or The crosslinking agent is a crosslinking agent with three or more functionalities, selected from triallyl cyanurate, triallyl isocyanurate, ethylene glycol dimethacrylate, trimethylallyl isocyanate and trimethylolpropane trimethacrylate, or a combination thereof.

5. The photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity according to claim 1 or 2, characterized in that: The raw materials for preparing the isolation microspheres further include the following components in parts by weight: 10-20 parts of dispersion stabilizer, Inhibitor 0.1-1 part.

6. The photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity according to claim 5, characterized in that: The dispersion stabilizer is selected from polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and polyvinyl pyrrolidone, or a combination thereof, and / or The inhibitor is selected from sodium nitrite, methylene blue, sodium sulfide, thiourea, sodium sulfate, ammonium thiocyanate, or a combination thereof, more preferably, sodium nitrite.

7. A photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity as claimed in any one of claims 1 to 6, characterized in that: The preparation method of the isolated microspheres comprises the following steps: (1) Preparation of oil phase: 60 to 120 parts by weight of acrylic acid ester monomer, 0 to 35 parts by weight of styrene monomer, 0.01 to 2 parts by weight of initiator and 1 to 10 parts by weight of crosslinking agent are mixed at 0 to 40° C. to prepare an oil phase; (2) Preparation of aqueous phase: Add 10 to 20 parts by weight of a dispersion stabilizer and 0.1 to 1 part by weight of a polymerization inhibitor to 150 to 250 parts by weight of deionized water, and stir to form an aqueous phase; (3) homogenizing the water phase and the oil phase: pouring the oil phase prepared in step (1) into the water phase prepared in step (2), and homogenizing the mixed liquid to form a suspension; (4) Preparation of microsphere reaction: The suspension obtained in step (3) is transferred into a reaction vessel and reacted at 40-100° C. for 15-30 h in an inert gas atmosphere. The milky white liquid obtained after the reaction is filtered, washed with deionized water, and then dried to obtain the isolated microspheres.

8. The photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity according to claim 7, characterized in that: In the preparation method, In step (3), homogenization is performed using a homogenization device, the homogenization speed is 200 to 1000 rpm, the homogenization time is 10 to 40 min, and / or In step (4), the inert gas is selected from nitrogen, argon or helium.

9. The photovoltaic glass mildew-proof powder with high mildew resistance and high fluidity according to any one of claims 1 to 6, characterized in that: The photovoltaic glass mildew-proof powder comprises the following components in percentage by weight:

10. The photovoltaic glass mildew-proof powder according to claim 9, characterized in that: The organic acid is selected from maleic acid, adipic acid, cyclohexylbutyric acid, fumaric acid, or a combination thereof, more preferably, adipic acid, and / or The inorganic acid is selected from boric acid, tartaric acid, or a combination thereof, more preferably, boric acid, and / or The inorganic nanomaterial is selected from fumed silica, nano calcium carbonate, or a combination thereof, more preferably, fumed silica.